2018
DOI: 10.1097/md.0000000000013312
|View full text |Cite
|
Sign up to set email alerts
|

Suspended over length biliary stents versus conventional plastic biliary stents for the treatment of biliary stricture

Abstract: To compare patency between suspended over length biliary stents (SOBSs; made from nasobiliary tube) and conventional plastic biliary stents (CPBSs). We retrospectively analyzed 61 patients with extrahepatic biliary stricture who underwent SOBS placement (intrahepatic bile duct) and 74 patients who underwent CPBS placement. Stent patency and complications were compared. The SOBS group was slightly older and contained more females than the CPBS group but other baseline characteristics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Mechanical lithotripsy (ML; Trapezoid Rx; Boston Scientific) was performed for lithotripsy in case of stones larger than the diameter of the distal CBD, or if difficulty was encountered when using a Dormia basket for removal. A 7.5 Fr × 26 cm biliary plastic stent, a suspended overlength biliary stent made from a nasobiliary drainage tube (Boston Scientific), was placed to ensure that the biliary duct would not be clipped during endoclip papillaplasty and to reduce duodenobiliary reflux before follow‐up 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical lithotripsy (ML; Trapezoid Rx; Boston Scientific) was performed for lithotripsy in case of stones larger than the diameter of the distal CBD, or if difficulty was encountered when using a Dormia basket for removal. A 7.5 Fr × 26 cm biliary plastic stent, a suspended overlength biliary stent made from a nasobiliary drainage tube (Boston Scientific), was placed to ensure that the biliary duct would not be clipped during endoclip papillaplasty and to reduce duodenobiliary reflux before follow‐up 7 …”
Section: Methodsmentioning
confidence: 99%
“…A 7.5 Fr 9 26 cm biliary plastic stent, a suspended overlength biliary stent made from a nasobiliary drainage tube (Boston Scientific), was placed to ensure that the biliary duct would not be clipped during endoclip papillaplasty and to reduce duodenobiliary reflux before follow-up. 7 The complete removal of choledocholithiasis was defined as the absence of any filling defect on balloon occlusion cholangiogram after negative ductal swept by balloon and/or basket. Prophylactic pancreatic stent was placed in the conditions where the guidewire was placed into the pancreatic duct three times and/or the pancreatic duct sphincter was pre-cut.…”
Section: Endoscopic Interventionsmentioning
confidence: 99%
“…9 On the contrary, a Chinese study by Yan et al highlighted that over length suspended plastic stents have improved patency periods compared to conventional plastic stents. 10 Again, this study was retrospective and single center based with a limited number of patients and the results cannot be generalized.…”
mentioning
confidence: 92%
“…In a RCT study conducted in Denmark by Pedersen et al, it was concluded that there was increased stent migration among the stents placed above the sphincter of Oddi compared to the transpapillary approach ( p =0.026), whereas no difference in overall stent performance was noted among the two groups [ 9 ]. On the contrary, a Chinese study by Yan et al highlighted that over length suspended plastic stents have improved patency periods compared to conventional plastic stents [ 10 ]. Again, this study was retrospective and single center based with a limited number of patients and the results cannot be generalized.…”
mentioning
confidence: 99%
“…However, the interventions were repeated monthly because of stent migrations. After several failing attempts at stent secure schemes, using clips with nylon drawstrings at both the proximal and distal ends, we finally fasten a 7F 200-mm stent (remolded from our suspended overlength biliary stent [ 1 ] ) at the gastric wall [Figure 4 ]. The patient had remained asymptomatic until now.…”
mentioning
confidence: 99%